Taphonomy at Kalkbank: a Late Pleistocence site in the Limpopo Province, South Africa - Hutson, Jarod Mark (My University, 2006)
Drawing on the large body of taphonomic, ethnoarchaeological, and general zooarchaeological literature currently available, the main goal of this research report is to provide the first comprehensive taphonomic account of the fauna at Kalkbank in order to establish whether humans, carnivores, or other natural processes were the major accumulators of the assemblage. Through examination of species presence and abundance, patterns of bone breakage, various surface modifications to the bones, several aspects of skeletal part representation, and mortality profiles, it has been proven that carnivores were the main agent of accumulation. Furthermore, it has been determined that the site accumulated sometime during the late Pleistocene, but closely resembles several open-air sites dated from the Acheulean.
Keywords: Taphonomy; Kalkbank; Faunal Analysis